A novel nicastrin mutation in a three‐generation Dutch family with hidradenitis suppurativa: a search for functional significance. (12th March 2020) - Vossen, A.R.J.V.; van Straalen, K.R.; Swagemakers, S.M.A.; de Klein, J.E.M.M.; Stubbs, A.P.; Venter, D.J.; van der Zee, H.H.; van der Spek, P.J.; Prens, E.P.
Abstract: Background: Mutations in the γ‐secretase enzyme subunits have been described in multiple kindreds with familial hidradenitis suppurativa (HS). Objective: In this study, we report a novel nicastrin ( NCSTN) mutation causing HS in a Dutch family. We sought to explore the immunobiological function of NCSTN mutations using data of the Immunological Genome Project. Methods: Blood samples of three affected and two unaffected family members were collected. Whole‐genome sequencing was performed using genomic DNA isolated from peripheral blood leucocytes. Sanger sequencing was done to confirm the causative NCSTN variant and the familial segregation. The microarray data set of the Immunological Genome Project was used for thorough dissection of the expression and function of wildtype NCSTN in the immune system. Results: In a family consisting of 23 members, we found an autosomal dominant inheritance pattern of HS and detected a novel splice site mutation (c.1912_1915delCAGT) in the NCSTN gene resulting in a frameshift and subsequent premature stop. All affected individuals had HS lesions on non‐flexural and atypical locations. Wildtype NCSTN appears to be upregulated in myeloid cells like monocytes and macrophages, and in mesenchymal cells such as fibroblastic reticular cells and fibroblasts. In addition, within the 25 highest co‐expressed genes with NCSTN we identified CAPNS1, ARNT and PPARD . Conclusion: This study reports the identification a novel NCSTN gene splice site mutation which causes familial HS. The associated immunobiological functions of NCSTN and its co‐expressed genes ARNT and PPARD link genetics to the most common environmental and metabolic HS risk factors which are smoking and obesity.